Axon guidance and injury – lessons from Wnts and Wnt signaling - Onishi, Keisuke (Curr Opin Neurobiol, 2014)
Many studies in the past decade have revealed the role and mechanisms of Wnt signaling in axon guidance during development and the reinduction of Wnt signaling in adult axons upon traumatic injury, which has profound influences on axon plasticity. With 19 Wnts and 14 known receptors (10 Frizzleds (Fzds), Ryk, Ror1/2 and PTK7), the Wnt family signaling molecules contribute significantly to the wiring specificity of the complex brain and spinal cord circuitry. Subsequent investigation into the signaling mechanisms showed that conserved cell polarity pathways mediate growth cone steering. These cell polarity pathways may unveil general principles of growth cone guidance. The reappeared Wnt signaling system after spinal cord injury limits the regrowth of both descending and ascending motor and sensory axons. Therefore, the knowledge of Wnt signaling mechanisms learned from axon development can be applied to axon repair in adulthood.